2007
DOI: 10.1042/bj20070984
|View full text |Cite
|
Sign up to set email alerts
|

Trimerization of collagen IX α-chains does not require the presence of the COL1 and NC1 domains

Abstract: Collagen IX is a heterotrimer of three alpha-chains, which consists of three COL domains (collagenous domains) (COL1-COL3) and four NC domains (non-collagenous domains) (NC1-NC4), numbered from the C-terminus. Although collagen IX chains have been shown to associate via their C-terminal NC1 domains and form a triple helix starting from the COL1 domain, it is not known whether chain association can occur at other sites and whether other collagenous and non-collagenous regions are involved. To address this quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 35 publications
0
9
3
Order By: Relevance
“…The trimerization properties and stabilization of the collagen triple helix on either end of the NC2 domain suggests a universal role for this domain in chain selection, chain registration, and initiation of the triple helix formation in all FACIT collagens. This is somewhat in contradiction with studies on collagen IX, where others believe that the COL2-NC2 region alone is not sufficient for trimerization (7). Although this might reflect a different role of the NC2 domain in type IX collagen, a more detailed analysis is required.…”
Section: Discussioncontrasting
confidence: 63%
See 2 more Smart Citations
“…The trimerization properties and stabilization of the collagen triple helix on either end of the NC2 domain suggests a universal role for this domain in chain selection, chain registration, and initiation of the triple helix formation in all FACIT collagens. This is somewhat in contradiction with studies on collagen IX, where others believe that the COL2-NC2 region alone is not sufficient for trimerization (7). Although this might reflect a different role of the NC2 domain in type IX collagen, a more detailed analysis is required.…”
Section: Discussioncontrasting
confidence: 63%
“…Contrary to these studies, very recent studies on collagen IX show that three ␣-chains can associate in the absence of the COL1 and NC1 domains to form a triple helix, although the COL2-NC2 region alone is not sufficient for trimerization (7). This suggests that folding and chain selection of collagen IX is a cooperative process involving multiple COL and NC domains (7). It has also been hypothesized that the NC2 domain of all FACIT collagens is able to form an ␣-helical coiled-coil, thus bearing an ability to trimerize those collagens (8), but no experimental evidence has been reported so far.…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…On the other hand, a recent study of full-length protein and several deletion mutants expressed in insect cells showed that COL1 and NC1 are not required for trimerization of collagen IX, although the COL1-NC1 region might be important for chain specificity (16). Additionally, the authors reported that the COL2-NC2 region of collagen IX is not sufficient for trimerization (16).To explore the trimerization potential of the collagen IX, we have studied folding and stability of the NC2 domain alone as well as in junction with a collagenous sequence containing the type III collagen cystine knot. The cystine knot naturally found in type III collagen is located at the end of the collagenous domain and forms interchain disulfide bonds.…”
mentioning
confidence: 99%
“…On the other hand, a recent study of full-length protein and several deletion mutants expressed in insect cells showed that COL1 and NC1 are not required for trimerization of collagen IX, although the COL1-NC1 region might be important for chain specificity (16). Additionally, the authors reported that the COL2-NC2 region of collagen IX is not sufficient for trimerization (16).…”
mentioning
confidence: 99%